2014
DOI: 10.1113/jphysiol.2013.268573
|View full text |Cite
|
Sign up to set email alerts
|

Reflex control of inflammation by sympathetic nerves, not the vagus

Abstract: Key pointsr It is believed that the CNS controls inflammation via the autonomic nervous system, but the strength of this action and the neural pathways responsible are unclear.r In anaesthetized rats we measured the inflammatory response to lipopolysaccharide (LPS, 60 μg kg −1 , I.V.) by plasma tumour necrosis factor α (TNFα) levels 90 min later.r Bilateral section of the splanchnic sympathetic nerves before LPS treatment resulted in a 5-fold increase in the plasma TNFα response, but bilateral vagotomy had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
252
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(272 citation statements)
references
References 43 publications
13
252
2
5
Order By: Relevance
“…More specifically, vagal preganglionic neurons were thought to contact and activate noradrenergic postganglionic neurons coursing in the splenic nerve. However, no anatomical or electrophysiological evidence of such synapses has been found (38), and we have confirmed that VNS does not elicit a detectable evoked response in the splenic nerve of anesthetized rats (C. Abe, unpublished observations). Interestingly, the spleen seems to be an exception among +/-(α7HE), and α7KO mice underwent VNS 24 hours prior to IRI.…”
Section: Neural Pathways Responsible For the Protective Effect Of Vnssupporting
confidence: 51%
See 1 more Smart Citation
“…More specifically, vagal preganglionic neurons were thought to contact and activate noradrenergic postganglionic neurons coursing in the splenic nerve. However, no anatomical or electrophysiological evidence of such synapses has been found (38), and we have confirmed that VNS does not elicit a detectable evoked response in the splenic nerve of anesthetized rats (C. Abe, unpublished observations). Interestingly, the spleen seems to be an exception among +/-(α7HE), and α7KO mice underwent VNS 24 hours prior to IRI.…”
Section: Neural Pathways Responsible For the Protective Effect Of Vnssupporting
confidence: 51%
“…Clearly, under anesthesia, vagal afferent stimulation evokes a response in sympathetic nerves and this response does have an excitatory component (29). In addition, the sympathetic system facilitates the rapid inflammatory response (increased TNF-α) elicited by an acute injection of LPS in anesthetized rats (38). However, the vagosympathetic reflex hypothesis does not explain satisfactorily why the antiinflammatory effect is elicited by stimulating the peripheral end of the cut vagus nerve (24), an observation replicated in the present renal ischemia model; this hypothesis also does not explain why the protective effect of VNS is delayed (VNS done 10 minutes before ischemia offers no protection) and long lasting (at least 2 days).…”
Section: 6mentioning
confidence: 99%
“…24 Nevertheless, vagus nerve stimulation by centrally acting muscarinic agonists, such as CNI-1493, has been shown to suppress peripheral inflammatory responses that can be prevented by vagotomy, demonstrating that the vagus is an essential efferent pathway of the central cholinergic antiinflammatory pathway. 25 Assessment of HRV has been recognized to provide reliable, noninvasive information on the activity of the autonomic nervous system, including its vagal and sympathetic components.…”
Section: Strokementioning
confidence: 99%
“…in the splenic nerve, as initially thought (11). Moreover, vagal stimulation does not produce an evoked response in the splenic nerve, indicating that a vagal-vagal reflex is unlikely to be a central mechanism of CAP activation.…”
Section: Discussionmentioning
confidence: 55%